Insulin increases placental triglyceride as a potential mechanism for fetal adiposity in maternal obesity - Anika K. Anam; Katherine M. Cooke; Milana Bochkur Dratver; Jane V. O'Bryan; Lauren E. Perley; Seth M. Guller; Janice J. Hwang; Hugh S. Taylor; Leigh Goedeke; Harvey J. Kliman; Daniel F. Vatner; Clare A. Flannery (Elsevier, 2022)
Objective: Maternal obesity increases the incidence of excess adiposity in newborns, resulting in lifelong diabetes risk. Elevated intrauterine fetal adiposity has been attributed to maternal hyperglycemia; however, this hypothesis does not account for the increased adiposity seen in newborns of mothers with obesity who have euglycemia. We aimed to explore the placental response to maternal hyperinsulinemia and the effect of insulin-like growth factor 2 (IGF-2) in promoting fetal adiposity by increasing storage and availability of nutrients to the fetus. Methods: We used placental villous explants and isolated trophoblasts from normal weight and obese women to assess the effect of insulin and IGF-2 on triglyceride content and insulin receptor signaling. Stable isotope tracer methods were used ex vivo to determine effect of hormone treatment on de novo lipogenesis (DNL), fatty acid uptake, fatty acid oxidation, and esterification in the placenta. Results: Here we show that placentae from euglycemic women with normal weight and obesity both have abundant insulin receptor. Placental depth and triglyceride were greater in women with obesity compared with normal weight women. In syncytialized placental trophoblasts and villous explants, insulin and IGF-2 activate insulin receptor, induce expression of lipogenic transcription factor SREBP-1 (sterol regulatory element-binding protein 1), and stimulate triglyceride accumulation. We demonstrate elevated triglyceride is attributable to increased esterification of fatty acids, without contribution from DNL and without an acceleration of fatty acid uptake. Conclusions: Our work reveals that obesity-driven aberrations in maternal metabolism, such as hyperinsulinemia, alter placental metabolism in euglycemic conditions, and may explain the higher prevalence of excess adiposity in the newborns of obese women.